Refleksi Tentang Penginjilan, Kristenisasi, dan Moderasi Beragama di Era Modern. - Yuni Pancarani (LOGON ZOES: Jurnal Teologi, Sosial dan Budaya, 2024)
Evangelism and Christianization activities in the modern era face major challenges marked by technological developments, globalization and high religious plurality. Therefore, the main problem that needs to be answered is how evangelization methods can be adapted to utilize digital technology and social media effectively while still maintaining ethics and respecting diversity, as well as how Christianization can be carried out in a multicultural society by respecting local cultural values and building dialogue. inter-religious. Apart from that, the important role of religious moderation in facilitating dialogue and building harmony amidst efforts to evangelize and Christianize is also a problem that needs to be resolved. The aim of this research is to understand the evolution of evangelization methods in the digital era and its ethical implications, explore the dynamics of Christianization in a multicultural context, and analyze the role of religious moderation as a bridge for interreligious dialogue. The research results show that evangelization in the digital era requires an ethical and responsible approach, while Christianization in a multicultural context requires respect for cultural and religious diversity. Religious moderation was found to be a key factor in facilitating interfaith dialogue and building social harmony. The discussion in this research emphasizes that effective Christianization in the modern era must be inclusive, dialogical, and accommodate local cultural values. This research underlines the importance of tolerance, cooperation, education and conflict resolution in building positive inter-religious relations.Kegiatan penginjilan dan kristenisasi di era modern menghadapi tantangan besar yang ditandai oleh perkembangan teknologi, globalisasi, dan pluralitas agama yang tinggi. Oleh karena itu, masalah utama yang perlu dijawab adalah bagaimana metode penginjilan dapat diadaptasikan agar memanfaatkan teknologi digital dan media sosial secara efektif namun tetap menjaga etika dan menghormati keragaman, serta bagaimana kristenisasi dapat dilakukan di masyarakat multikultural dengan menghormati nilai-nilai budaya lokal dan membangun dialog antarumat beragama. Selain itu, pentingnya peran moderasi beragama dalam memfasilitasi dialog dan membangun kerukunan di tengah upaya penginjilan dan kristenisasi juga menjadi masalah yang perlu diselesaikan. Tujuan dari penelitian ini adalah untuk memahami evolusi metode penginjilan di era digital beserta implikasi etisnya, mengeksplorasi dinamika kristenisasi dalam konteks multikultural, serta menganalisis peran moderasi beragama sebagai jembatan dialog antaragama. Hasil penelitian menunjukkan bahwa penginjilan di era digital memerlukan pendekatan yang etis dan bertanggung jawab, sementara kristenisasi dalam konteks multikultural membutuhkan penghormatan terhadap keragaman budaya dan agama. Moderasi beragama ditemukan sebagai faktor kunci dalam memfasilitasi dialog antaragama dan membangun harmoni sosial. Pembahasan dalam penelitian ini menekankan bahwa kristenisasi yang efektif di era modern harus inklusif, dialogis, dan mengakomodasi nilai-nilai budaya setempat. Penelitian ini menggarisbawahi pentingnya toleransi, kerjasama, pendidikan, dan resolusi konflik dalam membangun hubungan antarumat beragama yang positif.